Early discharge in gynecological laparoscopy. - Díaz, Augusto (2015)
OBJECTIVE: To evaluate the cases and gynecological laparoscopic management during 1998 in the Central Program Specialties (PCE) EsSalud. MATERIALS AND METHODS: Of the 4460 operations carried out by the PCE in 1998, 792 cases for all gynecological laparoscopic surgery is assessed. Patients were hospitalized two hours before surgery and discharged on average 24 hours. RESULTS: Of the 792 interventions, 308 were for infertility, ovarian cyst 153, 117 pelvic inflammatory disease, polycystic ovary 79. 62 adherence syndrome, 24 fibroids, ectopic pregnancy 13 11 ovarian cyst, dermoid cyst nine six hydrosalpinx. Complications occurred in 1.5% of cases, six of them omalgia four wound infection, one acute abdomen and one rectal laceration sigmoid. The average stay was 34 hours and the successful recovery. CONCLUSION: The lower incidence of complications, shorter hospital stay and lower morbidity rate in our series, has enabled us to reduce costs and enjoy acceptance of patients.